S2 Nocturnal hypoxaemia rather than obstructive sleep apnoea is associated with progressive deterioration in quality of life in patients with fibrotic interstitial lung disease. (11th November 2022) - Myall, KJ; West, AG; Martinovic, JL; Lam, JL; Roque, D; Domi, V; Wu, Z; Jackson, DJ; Maher, T; Molyneaux, PL; Suh, ES; Kent, BD
Abstract : Introduction and Objectives: Both nocturnal hypoxaemia (NH) and obstructive sleep apnoea (OSA) are common in patients with interstitial lung disease (ILD) and may impact on quality of life. We prospectively examined the relationship between sleep breathing characteristics and disease-specific quality of life measures. Methods: We performed a prospective observational study of patients with an MDT diagnosis of a fibrotic ILD, who did not have resting hypoxaemia. All underwent a home sleep study at enrolment and completed a King's Brief Interstitial Lung Disease (KBILD) questionnaire at 6 and 12 months. NH was defined as >10% of sleep with SpO2 <90%. OSA was defined as an apnoea-hypopnea index of >15 events/hr. A change in KBILD score of >4 was considered of clinical relevance. Two-way ANOVA was used to examine relationships between NH and OSA and quality of life over time. Results: Among 102 (male 74.5%; age 73.0±8.7 years; FVC 2.74±0.78L; 91.1% idiopathic pulmonary fibrosis) participants, 20 (19.6%) demonstrated prolonged nocturnal hypoxaemia (NH), and 32 (31.4%) had obstructive sleep apnoea (OSA). There were no significant differences between those with and without NH or OSA at baseline. Despite this, NH was associated with a more rapid decline in both quality of life as measured by the KBILD (-16.9 ± 10.2 in the NH group compared with -4.8 ± 9.6 in the group without, p = 0.005). OSA in the absence of NH was not associated with greater deteriorations in KBILD score (-10.2 ±10.8 in the OSA group compared with – 6.6 ± 12.4 in the group without, p=0.46). Moreover, the presence of NH also predicted increased likelihood of death over 12 months of follow up (hazard ratio 2.78; 95% confidence interval, 0.85–9.12, p=0.19). Conclusions: NH, but not OSA, predicted a more rapid decline in disease related quality of life over time in patients with fibrotic ILD. This supports further work to investigate interventions in sleep to improve patients' quality of life.